Haemophilus paragallinarum in chickens in Indonesia: III. Antimicrobial drug sensitivity test ofHaemophilus paragallinarum from chickens suffering of coryza - Sri Poernomo; Sutarma Sutarma; Sang Ayu Ketut Dewi Silawatri (Jurnal Ilmu Ternak dan Veteriner, 1998)
An agar disc diffusion method was used to examine the sensitivity of 27 Haemophilus paragallinarum (Hpg) isolates consisted of 23 local isolates, 4 standard isolates (serotype A) and Escherichia coli ATCC 24922 as a control to eight antimicrobial drugs (ampicillin, erythromycin, oxytetracycline, doxycycline, neomycin, streptomycin, colistine and sulphanlethoxazole-trimethoprim) . Twenty one out of 23 local isolates of Hpg were sensitive to doxycycline, 19 isolates to ampsllin, 18 isolates to oxytetracycline, 17 isolates to sulphametoxazole-trimethoprim, 16 isolates to erythromycin, and 13 isolates to neomycin, while 13 isolates were resistance to colistine and 11 isolates were also resistance to streptomycin .   Keywords : Haemophilus paragallinarum, chicken, coryza, sensitivity test, antimicrobial drug